Surface waviness of weld bead (layer) of GTAW based wire arc additive manufacturing process - Agus Sentana; Syahbardia; Mabel Agung Nugroho; Ario Sunar Baskoro (Teknobiz : Jurnal Ilmiah Program Studi Magister Teknik Mesin, 2026)
Additive manufacturing has become a focus of industry and research due to the many new developments in processes and systems. This is further strengthened by the trend of resource efficiency, as manufacturing processes towards additive manufacturing offer the possibility of producing close to the required size shape. Additive manufactured products can experience surface imperfections assessed in this study, namely the morphology profile or surface curvature (surface waviness) of the weld bead layer. Generally, surface curvature can be referred to as a "hump" caused by the welding process. To achieve the target of achieving products with relatively minimal surface waviness, experiments and analysis of the manufacturing process using GTAW additive welding on AA 6061 substrate material with ER 5356 filler were conducted. The experiments were carried out by first determining the process parameters and factors that affect the quality of the weld bead layer. The layers stacked in layers were measured for their width and height geometry, surface waviness tests were conducted, and analysis was carried out. The deposition rate or filler deposit, travel speed, and filler feed speed determine the level of surface waviness. In this study, high surface curvature occurred at a wire feeder speed (WFS) of 25 mm/s with a travel speed (TS) of 80 mm/min.